Near-infrared glucose sensing in adulterated honey using smartphone-based photometric detection: A feasibility study - Nazir, Muhammad Alif Danial Mohd (Universiti Sains Malaysia, 2025)
Glucose sensing is vital in health such as monitoring glucose levels in managing diabetes and food quality, for instance, adulterated honey detection. Current methods involve invasive, expensive equipment and highly trained personnel to carry out the test, which can limit the detection and application of glucose at on-site determination. This study aimed to apply smartphone-based biophotonic instrumentation for measuring glucose concentrations using the photometric method. The photonic device constructed consists of a 940 nm near-infrared lightemitting diode (NIR LED) as an emitter, a BPW34 photodiode as a detector, a Raspberry Pi Pico microcontroller board acts as a digital interface to convert the receiving data into output voltage, and an Android app; Scoppy as a digital oscilloscope to display the output voltage value on a smartphone. The instrument detected the glucose at different concentrations. A lower and higher range of glucose concentrations was tested which is 10 – 100 g/dL for glucose in adulterated honey. The findings indicated that higher glucose concentrations resulted in higher detector output voltages. The linear regression analysis obtained is R2 = 0.4038 with slope value of -0.0019 for phototransmittance and R2 = 0.4504 with slope value of 0.0011 for photo absorbance